2015
DOI: 10.1007/s00420-015-1041-2
|View full text |Cite
|
Sign up to set email alerts
|

The ordinary work environment increases symptoms from eyes and airways in mild steel welders

Abstract: Purpose We aimed to follow diary-registered symptoms from eyes and airways in mild steel welders and relate them to different exposure measures. Furthermore, we would clarify the influence of possible effect modifiers.Methods Non-smoking welders with (N = 74) and without (N = 32) work-related symptoms the last month were enroled. Symptoms and work tasks each day for three two-week periods during 1 year were obtained. Respirable dust (RD) was measured 1 day each period for each worker. The personal daily exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…However, studies have shown that, in MS welders, respiratory symptoms clearly increase during working days, although the exposure was not extreme compared to the current exposure limit [173]. More recently, Monse et al [174] reported a concentration-response relationship with nano-sized ZnO particles in a low concentration range was, with systemic inflammatory effects of inhaled nano-sized ZnO particles, observed at concentrations well below the occupational exposure limit for ZnO.…”
Section: Occupational Exposure Limitsmentioning
confidence: 98%
“…However, studies have shown that, in MS welders, respiratory symptoms clearly increase during working days, although the exposure was not extreme compared to the current exposure limit [173]. More recently, Monse et al [174] reported a concentration-response relationship with nano-sized ZnO particles in a low concentration range was, with systemic inflammatory effects of inhaled nano-sized ZnO particles, observed at concentrations well below the occupational exposure limit for ZnO.…”
Section: Occupational Exposure Limitsmentioning
confidence: 98%
“…It has been shown that although the exposure levels do not normally exceed current Swedish permissible occupational exposure limits for inorganic respiratory dust (5 mg/m 3 ), there is a high frequency of upper and lower respiratory symptoms among welders [ 11 , 12 ]. Previous studies have suggested that welding particle exposure induces oxidative stress and an inflammatory response [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…at grinding the welded material (Zimmer and Maynard 2002 ). In an earlier study, we found that although the symptoms in welders increased significantly during working days the association with the welding exposure was not clear (Jönsson et al 2015 ). As the welders also ground the welded material, it was difficult to conclude to what degree the symptoms were elicited by the welding fumes.…”
Section: Introductionmentioning
confidence: 83%
“…In a previous study we found increased symptoms in welders during working days. The welders were in this study exposed not only to welding fumes, but also to particles from grinding (Jönsson et al 2015 ). In the present study the participants were only exposed to welding fumes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation